El proceso de acompañamiento pedagógico formativo como condicionante de la comprensión textual de los niños en educación básica: el caso de los grados 4to y 5to entre 2015- 2016 del Centro Educativo el Manzanillo de la ciudad de Medellín (2017)
This work reflects about the pedagogical-formative accompaniment made to the reading-writing process, with students of primary education at the El Manzanillo Educational Center in Medellín city. This is an analysis of the documents from the internal and external institutional evaluation, confronted with the production of some of the national and global theorists regarding the comprehensive Reading, also the diagnoses and observations of some teachers was keeped in acount. This study was developed with a random group of students of 4th and 5th grade, that for purposes of the investigation will be understood as sample population. The problematizing question was chosen: How has the process of accompaniment of the teachers to the performances of the students in terms of textual comprehension, in the Educational Center the Manzanillo in Medellín city? Textual understanding has been understood as the product of social accompanying practices. Among the many accompanying practices, the focus is built on the student teaching relationship from the use of appropriate tools. It is proposed then; From there, a set of improvement actions for the work was proposed with the child population that comes to the institution. It is considered that for the present of the local educational reality, this type of research of school character is pertinent, because it gives account of the different configurations and motivations that have to face the textual comprehension, transversalized by the world of the life of the children and of those who accompany them.